PENINGKATAN KESEJAHTERAAN MASYARAKAT PESISIR DI KOTA BATAM MELALUI PEMBERDAYAAN MASYARAKAT - Qodriyatun, Sri Nurhayati (Jurnal Aspirasi, 2013)
High economic growth in Batam has been marginalized local communities. They were living in coastal areal as a fishing community and live in poverty. Government of Batam has a variety of empowerment programs to improve the well-being live of them. But it still unsuccessful because the empowerment program only give them capital, lacking in securing access of community to natural resources. Coastal natural resources are assets for coastal communities. Therefore, there are two main things that must be done to empower coastal communities, which provide security of access to natural resources and provide capital for business.